Occurrence of Staphylococcus spp. in the wastewaters from Iran: Diversity, antimicrobial resistance, and virulence potential - Mahsa Ranjbar Omid; Houshang Jamali; Farshid Kafilzadeh; Amir Borjian; Mohsen Arzanlou (IWA Publishing, 2023)
The prevalence, antibiotic resistance, and virulence characteristics of Staphylococci from hospitals, livestock, municipals, and poultry wastewaters were investigated in Ardabil, Iran. From 155 staphylococcal isolates, 44.5% were coagulase-positive Staphylococcus (CoPS) and 55.5% were coagulase-negative Staphylococcus (CoNS) spp. Both CoPS and CoNS species were mainly found in hospital and poultry wastewater samples. The most prominent CoPS and CoNS species were Staphylococcus aureus at 80% and Staphylococcus xylosus at 37%. Methicillin resistance was found in 2% of S. aureus isolates. Overall, 49.2% of CoPS and 47.6% of CoNS isolates exhibited multidrug resistance phenotypes. CoPS isolates were the most resistant to penicillin (89%) and erythromycin (62%) and CoNS isolates exhibited the highest resistance to erythromycin (55%) and tetracycline (49%). Inducible clindamycin resistance was detected in 11% of S. aureus isolates. The ermC and aac genes were detected as the most common macrolide-lincosamide-streptogramin B and aminoglycoside-resistance encoding genes in 82.5 and 22.5% of S. aureus isolates, respectively. Most of the S. aureus isolates were positive for multiple virulence factors. The methicillin-resistant S. aureus isolates belonged to SCCmec type V. A new spa type t19215 was also identified. The occurrence of multidrug-resistant S. aureus with diverse genetic resistance and virulence background in wastewater is of great health concern. HIGHLIGHTS Ten coagulase-negative and four coagulase-positive Staphylococcus spp. were identified in wastewaters in Iran.; 50% of both coagulase-negative and coagulase-positive Staphylococcus spp. isolates were multidrug-resistant.; Occurrence of methicillin-resistant S. aureus was rare in wastewater samples in Iran.; S. aureus isolates with high virulence potentials were common.; A new spa type t19215 was identified in S. aureus isolates.;